2021
DOI: 10.37290/ctnr2641-452x.19:326-332
|View full text |Cite
|
Sign up to set email alerts
|

Forsythiaside-A Alleviates Traumatic Brain Injury by Regulating Toll-Like Receptor 4/Myeloid Differentiation Factor 88/Nuclear Factor-Kappa B Signaling Pathway

Abstract: Traumatic brain injury refers to brain injury caused by mechanical impact often leading to severe morbidity and mortality. Despite increasing awareness, there are no effective treatments strategies. Therefore, there is a need to develop new effective treatments for this injury. Forsythiaside A is a monomer of phenylethanolglucoside extracted from Forsythia, which has a wide range of pharmacological properties including protective effects on brain tissue. Herein, using a rat model of traumatic brain injury, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Forsythiaside A, phillyrin, and phillygenin have been shown to have significant anti-inflammatory and antioxidant activities in previous studies, but there are few studies on their comparison of effects ( Yuan et al, 2014 ; Ma et al, 2019 ; Du et al, 2020 ; Zhou et al, 2021a ; Tian et al, 2021 ). In this study, correlation analysis demonstrated that phillygenin and phillyrin, which belong to lignans, may be the main anti-inflammatory and antioxidant compounds of FF.…”
Section: Discussionmentioning
confidence: 99%
“…Forsythiaside A, phillyrin, and phillygenin have been shown to have significant anti-inflammatory and antioxidant activities in previous studies, but there are few studies on their comparison of effects ( Yuan et al, 2014 ; Ma et al, 2019 ; Du et al, 2020 ; Zhou et al, 2021a ; Tian et al, 2021 ). In this study, correlation analysis demonstrated that phillygenin and phillyrin, which belong to lignans, may be the main anti-inflammatory and antioxidant compounds of FF.…”
Section: Discussionmentioning
confidence: 99%